2013
DOI: 10.1109/access.2013.2262916
|View full text |Cite
|
Sign up to set email alerts
|

Template Aging Phenomenon in Iris Recognition

Abstract: Biometric template aging is defined as an increase in recognition error rate with increased time since enrollment. It is believed that template aging does not occur for iris recognition. Several research groups, however, have recently reported experimental results showing that iris template aging does occur. This template aging effect manifests as a shift in the authentic distribution, resulting in an increased false nonmatch rate. Analyzing results from a three-year time-lapse data set, we find ∼ 150% increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Iris template aging studies that compare, for the same set of subjects, the false non-match rate for short-time-lapse matches versus the false non-match rate (FNMR) for longtime-lapse matches, find an increased FNMR with additional elapsed time [2], [10]. This basic result has since been reported by other research groups analyzing other datasets.…”
Section: B Scientific Knowledge and Technical Advancementmentioning
confidence: 76%
See 1 more Smart Citation
“…Iris template aging studies that compare, for the same set of subjects, the false non-match rate for short-time-lapse matches versus the false non-match rate (FNMR) for longtime-lapse matches, find an increased FNMR with additional elapsed time [2], [10]. This basic result has since been reported by other research groups analyzing other datasets.…”
Section: B Scientific Knowledge and Technical Advancementmentioning
confidence: 76%
“…Because of the continual change in the student population, there are constraints on the size of longitudinal studies readily supported [2], [10], [11]. The longest time lapse between a subject's first and last acquisition was 3666 days (10 years).…”
Section: Overview Of Data Collectionmentioning
confidence: 99%
“…They found the evidence for the effect of template aging and concluded that the changes will be visible at one year and increases with an increase in time. In this analysis, they had noticed that more than 50% of false matches were found with two years' time-lapse whereas near about 150% with three years lapse as investigated [12].…”
Section: Effect Of Template Aging On Iris Based Biometric Systemsmentioning
confidence: 78%
“…Due to successful spoofing attacks targeted at commercial iris sensors, numerous liveness detection methods were proposed at the sensor and software levels [13]. Temporal stability of iris patterns seems to be lower than initially believed [18,19,20,12,36] and hard to be estimated as we may observe even contradictory conclusions drawn from the same datasets [10,21]. New research in post-mortem iris recognition [42,41] reveals that it is possible to use this biometric characteristic in forensic applications.…”
Section: Iris Recognitionmentioning
confidence: 96%